Comparative Analysis of The Management of Modern and Salafiyah Islamic Boarding Schools in Indonesia: Analisa Komparatif Pengelolaan Pondok Pesantren Modern dan Salafiyah di Indonesia - Musoffa, Musoffa (STAI Publisistik Thawalib Jakarta, 2024)
Islamic boarding schools play a central role in Islamic education in Indonesia; however, differences in the management of modern and Salafiyah islamic boarding schools have created a need for a comparative study of their respective systems. This study analyzes the similarities and differences in managing modern and Salafiyah islamic boarding schools in Indonesia. The research was conducted through library research, collecting scientific articles from Google Scholar and Scopus through topic determination, literature review, source filtering, result analysis, and interpretation. The findings indicate that both modern and Salafiyah islamic boarding schools share the objective of shaping santri (students) to be religious and morally upright. Nonetheless, modern islamic boarding schools emphasize the integration of religious and general curricula with a holistic approach and a global orientation through proficiency in language and technology. In contrast, Salafiyah islamic boarding school focuses on mastery of classical Islamic texts (kitab kuning) and traditional teaching methods. Regarding leadership, the kyai (religious leader) is a central figure in both types, but modern islamic boarding schools apply a more structured management system. The output of modern islamic boarding schools includes graduates who are adaptive to contemporary changes, whereas Salafiyah islamic boarding school produces scholars with a deep understanding of classical Islamic sciences. In conclusion, despite sharing similar goals, the modern and Salafiyah islamic boarding schools differ in curriculum approach, teaching methods, leadership systems, and educational output orientation.